Green Connectivity In Metropolitan Jabodetabek: Climate Change and The Challenge of Urban Forest - Putri, Safira Maharani; Simarmata, Hendricus Andy (CSID Journal of Infrastructure Development, 2025)
Urban areas in Indonesia, particularly the Greater Jakarta metropolitan region (Jabodetabek), are increasingly experiencing the adverse effects of climate change, such as the Urban Heat Island (UHI) phenomenon. Rapid urbanization has contributed significantly to rising greenhouse gas emissions and deteriorating environmental quality. Urban forests are one of the key solutions to mitigate these impacts; however, their spatial distribution in Jabodetabek remains suboptimal and poorly connected. This study uses NDVI as a proxy for urban forest density, where “urban forest” refers to vegetated areas within cities as defined by Presidential Regulation No. 60/2020. The research addresses the following question: How has urban forest connectivity across Jabodetabek changed over a 30-year period? Using multi-temporal Landsat satellite imagery, the Normalized Difference Vegetation Index (NDVI) was employed to identify vegetation cover and assess temporal changes in urban forest density. NDVI values were processed using ArcPy in ArcMap, followed by spatial reclassification to identify areas of degradation or regeneration. The analysis reveals fragmented and disconnected urban forests across Jabodetabek, with some areas experiencing vegetation loss of up to 40.3%, while others show a gradual recovery of up to 33.9%. The dynamics along the Bekasi River indicate that upstream and downstream areas remain connected, but are disrupted in the peri-urban–to–suburban transition zone, creating ecological gaps that interrupt continuity. This challenge is further compounded in urban areas, particularly Jakarta, where urban forests are not yet ecologically or administratively connected. These findings emphasize the urgency of strengthening urban forest connectivity to enhance ecological resilience and climate adaptation in Jabodetabek.